Students’ Perceptions of Self-Efficacy in English Writing Ability: An Analysis of Fourth-Semester Students at the English Department of UIN Fatmawati Sukarno Bengkulu - Relin Mardhatillah; Fera Zasrianita; Yashori Revola (Yayasan Darussalam Bengkulu, 2025)
This study investigates the influence of self-efficacy on the English writing ability of fourth-semester students in the English Language Study Program at UIN Fatmawati Sukarno Bengkulu. Self-efficacy refers to an individual’s belief in their capability to accomplish specific tasks and achieve desired goals. In English writing, self-efficacy is considered essential because effective writing requires confidence, grammatical competence, vocabulary mastery, organization of ideas, and the ability to express thoughts clearly in written form. This research employed a quantitative method with a descriptive approach and a field research design. The population consisted of 61 fourth-semester students from the English Language Study Program, Faculty of Tarbiyah and Tadris, and all students were selected as the sample through a total sampling technique. Data were collected using a Likert-scale questionnaire and supported by documentation. The research instruments were tested for validity and reliability, while the data were analyzed using descriptive statistics, normality and linearity tests, t-test analysis, and the coefficient of determination (R²) with the assistance of SPSS version 25. The findings revealed that self-efficacy had a positive and significant effect on students’ English writing ability. The t-test showed a significance value of 0.000 (< 0.05) and a t-value of 8.038, which exceeded the t-table value of 1.999. Furthermore, the coefficient of determination (R²) was 0.523, indicating that self-efficacy contributed 52.3% to students’ English writing ability, while the remaining 47.7% was influenced by other factors beyond the scope of this study. In conclusion, self-efficacy plays a significant role in enhancing students’ English writing performance. Students with higher levels of self-confidence tend to demonstrate better achievement in writing tasks. Therefore, lecturers and educational institutions are encouraged to foster students’ self-efficacy to improve their academic writing skills.